COMPARISON OF PHENOTYPIC AND MOLECULAR-GENETIC PROPERTIES OF THE STRAINS NEISSERIA MENINGITIDIS ISOLATED FROM PATIENTS WITH GENERALIZED FORMS OF MENINGOCOCCAL INFECTION AND CARRIERS - E. A. Martens (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
.